PENERAPAN MODEL CONCEPTUAL UNDERSTANDING PROCEDURES UNTUK MENINGKATKAN SIKAP KEINGINTAHUAN(CURIOSITY) SISWA DALAM PEMBELAJARAN IPA FISIKA DI KELAS VII SMPN 4 PEKANBARU - Mega Purwanti; Fakhruddin Z Fakhruddin Z; Zuhdi Maa’ruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is to determine the gain of students’ curiousity to learning physics at SMPN 4 in Pekanbaru by applying the model of Conceptual Understanding Procedures (CUPs). Survey and Observation are applied to respondents consisting of 7th grade students at SMPN 4 in Pekanbaru. Data analysis is conducted by using Gain curiosity students of developed questionnaire responses that distributed to 36 students for experiment class and 34 students for control class. Observation is made by observing 2 groups of students from experiment class consisting 12 students each group. The results of this research indicate that the results of questionnaires and observations can be concluded that the implementation of models of Conceptual Understanding Procedures (CUPs) that have been applied to the class VII SMPN 4 in Pekanbaru can improve the curiosity of the students in the learning process.Key words : conceptual understanding procedures, curiosity